Design trends of the counterfeit product and the original competition: عبد الخالق سمين فتاح (Al-Academy, 2016)
The problem of the research represented by knowing the approaches which presented by knowing the design guides and the design styles which the imitation products enter upon it to be able to competitor the other original products .The research aim was to comparison the design approaches of the functional performance and the utilizations for the imitation and the original products , however the research limits contained study products samples of the kitchen electric equipments which available in local markets of Baghdad city for the period (2000 – 2013) .After the view of research back for the subject fundamental basics and investigating research sample to be complete to a group of results and conclusions and the most marked of her were :1.The suitable employment for both of the plastic and stainless steel materials (which they had many specifications distinguishing it from other materials from the healthy and the employment matters) swan efficiently in original samples , and its effect was not weak in imitation samples .2.The chromatic difference and touches for determinations of industrial product units warps with a solver from the attraction and making attention of the receiver firm , and may be the imitation products will surpass sometime the original by her shapes and its attractive colors